Solvency Requirements Effect on the Financial Performance of Merged Commercial Banks in Rwanda: A Case of Banque Populaire Du Rwanda Public Limited Company (BPR) Atlas Mara - Patrick, Rwakayigamba; Muiruri, Paul Munene (Journal of Advance Research in Applied Science (ISSN 2208-2352), 2021)
As the world is becoming global and competitive is growing at an increasing rate where firms are engaging themselves in the rivalry and banks are not left behind. One of the best strategies used by firms to penetrate into the competition is mergers. The purpose of the study was to evaluate the effect of solvency requirements on merged commercial banks in Rwanda. This study was guided by theories like shareholder’s wealth maximization theories, Trade –off theory of capital structure and the theory of Modigliani and Miller. The targeted population was 70 the employees of BPR Rwanda Atlas Mara being the sample size from the different departments by the help of purposive sampling technique. The researcher used the questionnaires to gather data and also the published information from the company websites and the information was interpreted by using Statistical Packages for Social Sciences (SPSS) version 21. The findings on solvency requirement had influence on the financial performance after merger efforts and the overall mean of 3.138 agreed with the statement. The Spearman’s Rho correlation coefficient is 0.674 implying that the variables used in subsequent regression modelling are not similar and thus, there are no multicollinearities. This means that 67.4% of the changes in the financial performance of firms is being affected by the merger process. The regression results indicated that the coefficient is positive (0.79) and the significant levels are less than 0.05 (P-value=0.0033). This indicates that banks engage in various merger activities in order to improve their financial performance. The study concludes that solvency requirements contribute to financial performance of commercial banks in Rwanda. The researcher recommended that banks should engage themselves in merger activities in order to maintain the competition since it got a bigger effect concerning the performance improvements.